Community Empowerment Through Digital-Based Local Economic Development In Society 5.0 Era - Kukuh Miroso Raharjo; Zulkarnain Zulkarnain; M Haidar (Universitas Negeri Padang, 2023)
Community empowerment is often carried out by change agents using various methods. Detailed, detailed and in-depth identification is the first step to empowering the community. The purpose of this study is to analyze the stages in community empowerment through digital-based local economic development in the era of society 5.0. The research method uses a qualitative approach with a case study type. The location of the research was carried out in the Labsite Village of the Department of Outer School Education with a total of three villages included in the Malang Regency area, namely Pait Village, Kasembon District, Benjor Village, Tumpang District, and Pujon Kidul Village, Pujon District. Data analysis uses the Miles and Huberman models which consist of three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that the stages in community empowerment through digital-based local economic development are carried out in two ways, starting with strengthening a solid production ecosystem through four stages, namely; (1) identification, (2) inventory, (3) management and development of assets, and (4) building partnership networks to introduce products. Furthermore, building a sustainable business ecosystem. Then, building a sustainable digital-based business ecosystem with three stages, namely, (1) Maintaining and Creating a Market, (2) Forming a Solid Network, and (3) Product Expansion using Digital Media